Passive and active measurement 12th International Conference, PAM 2011, Atlanta, GA, USA, March 20-22, 2011. Proceedings - Spring, Neil; Riley, George F. (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Passive and Active Measurement, PAM 2011, held in Atlanta, GA, USA, in March 2011. The 24 revised full papers presented were carefully reviewed and selected from 56 submissions. The papers were arranged into seven sessions covering passive measurement, wireless models, bandwidth, automated bots, route avoidance, interdomain protocols, timing, and diagnosis.